China’s Dollar-linked Hong Kong during the Global Crisis (2019)
This paper explores the domestic price level and trade competitiveness of Hong Kong in addition to the compatibility of this dollar-based currency board to the criteria inspired by the optimum currency area (OCA) theory. On price and competitiveness, findings point out that during the turmoil Hong Kong had not performed as well as that in the past and an apparent reason for this is the inflows of hot capital from abroad especially of the US that fuelled rising property prices. On conformity to the OCA criteria, the findings broadly corroborate the fixed exchange regime with the US as the monetary anchor country but at the same time China appears as a prospective contender to US as the monetary anchor. In the longer run, amidst the prolonged economic and monetary weaknesses in the US plus the emergence of renminbi as a global currency, Hong Kong might as well unify its exchange rate with the Chinese money.